2018
DOI: 10.1108/ijqrm-01-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Achieving better revenue and customers’ satisfaction with after-sales services

Abstract: Purpose Branded car dealerships with best revenue by serviced car also have the best after-sales customers’ satisfaction level. The purpose of this paper is to present the analysis of the after-sales quality management practices adopted by dealerships with the best performance in terms of customer’s satisfaction and revenue and how such practices contribute to these results. Design/methodology/approach A multiple case study was performed with nine leader branded car dealerships in an emerging country, consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
14
0
2
Order By: Relevance
“… Authors Methodology Factors identified Key findings 1 James et al, ( 2020 ) ISM and AHP in auto service quality 9 auto garage challenges New model proliferation, new technology and service quality are key drivers 2 James and James, ( 2020 ) Graph theory—auto-garage service quality 7 quality factors of auto service garage Garage ambience, Support system, technician capability and repair reliability, 3 Strydom et al, ( 2020 ) Conceptual model testing using SEM Seven automotive service related measures Service resources to enhance service quality, customer satisfaction and customer retention to improve profitability 4 Chatterjee et al, ( 2020 ) Hypothesis testing using validation through survey Factors study on adoption of AI integrated CRM system Perceived usefulness; perceived ease of use; utilitarian attitude and hedonic attitude are the four characteristics that impact AI integrated CRM system 5 Hassan et al, ( 2019 ) A survey of the 135 SMEs Understanding benefits of social CRM (s-CRM) Adoption of ICT has direct and indirect impacts on s-CRM performance. Perceived value of s-CRM was an influential factor for ICT adoption and customer information management 6 Raut et al, ( 2020 ) TISM—automotive service sector 10 Green human resource management factors ‘Green culture, adoption of green strategy,’ coupled with ‘Green training and development’ are the two driving factors 7 Borchardt et al, ( 2018 ) Case study—9 best branded car dealers 5 processes for customer satisfaction and revenue Leadershi...…”
Section: Literature Reviewmentioning
confidence: 99%
“… Authors Methodology Factors identified Key findings 1 James et al, ( 2020 ) ISM and AHP in auto service quality 9 auto garage challenges New model proliferation, new technology and service quality are key drivers 2 James and James, ( 2020 ) Graph theory—auto-garage service quality 7 quality factors of auto service garage Garage ambience, Support system, technician capability and repair reliability, 3 Strydom et al, ( 2020 ) Conceptual model testing using SEM Seven automotive service related measures Service resources to enhance service quality, customer satisfaction and customer retention to improve profitability 4 Chatterjee et al, ( 2020 ) Hypothesis testing using validation through survey Factors study on adoption of AI integrated CRM system Perceived usefulness; perceived ease of use; utilitarian attitude and hedonic attitude are the four characteristics that impact AI integrated CRM system 5 Hassan et al, ( 2019 ) A survey of the 135 SMEs Understanding benefits of social CRM (s-CRM) Adoption of ICT has direct and indirect impacts on s-CRM performance. Perceived value of s-CRM was an influential factor for ICT adoption and customer information management 6 Raut et al, ( 2020 ) TISM—automotive service sector 10 Green human resource management factors ‘Green culture, adoption of green strategy,’ coupled with ‘Green training and development’ are the two driving factors 7 Borchardt et al, ( 2018 ) Case study—9 best branded car dealers 5 processes for customer satisfaction and revenue Leadershi...…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ha et al (2016) discussed that, in manufacturing, service is just after-sales services, and it is vital as products. As addressed by Borchardt et al (2018), after-sales services are more sustainable income resource than the products. After-sales services can face with fluctuations in business via well-established connections with clients throughout the product life cycle.…”
Section: Case Studymentioning
confidence: 99%
“…In the automotive sector, Matzler et al (2004) evaluate only the attributes of the product and demonstrate that the quality of products is a key driver of satisfaction. Meanwhile Saccani et al (2006) and Borchardt, Souza, Pereira and Viegas (2018) evaluated the relevance of A/S satisfaction of car costumers. Thus, the present empirical research is opportune to support the notion that product attributes as well as after-sales service are critical aspects for consumers of durable goods such as cars.…”
Section: Testing Of the Research Modelmentioning
confidence: 99%